2007
DOI: 10.1002/jor.20358
|View full text |Cite
|
Sign up to set email alerts
|

Joint area constraint had no influence on bone loss in proximal tibia 5 years after total knee replacement

Abstract: After total knee replacement (TKR) the bone mineral density (BMD) decreases in the proximal tibia. Our aim was to evaluate if changes in constraint of the cemented AMK TKR (DePuy, Johnson & Johnson, Leeds, UK) had any effect on postoperative bone remodeling in the proximal tibia. We used dual-energy X-ray absorptiometry in 43-53 knees to record changes in BMD in three regions of interest around the tibial component up to 5 years after operation with the AMK (DePuy) TKR. The knees had been randomly allocated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Although the BMD decline in our patients has not resulted in clinical failure, longer-term remodeling is less clear. Some authors have reported stabilization of BMD by 2 years [7,8], with Saari et al [17] finding stable BMD loss out to 5 years. Others have reported ongoing loss at 3 years [4,11,12].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although the BMD decline in our patients has not resulted in clinical failure, longer-term remodeling is less clear. Some authors have reported stabilization of BMD by 2 years [7,8], with Saari et al [17] finding stable BMD loss out to 5 years. Others have reported ongoing loss at 3 years [4,11,12].…”
Section: Discussionmentioning
confidence: 98%
“…They reported mean tibial BMD loss of as much as 10% at 2 years but found no difference between groups. Saari et al [17] examined tibial BMD change in stemmed components with either posterior-stabilized or cruciate-retaining polyethylene inserts. Loading on the proximal tibia was theorized to differ between designs as a result of increased constraint in the posterior-stabilized knee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bone remodeling was simulated for a period of sixty months as the previous clinical evidence suggested that bone suffers 'memory loss' and the adaptive process stops after this period (Petersen et al, 1995;Saari et al, 2007).…”
Section: Bone Remodeling Simulationmentioning
confidence: 99%
“…Subsequent to the early studies mentioned above, clinical evidence has suggested that bone suffers 'memory loss' and the adaptive process stops after sixty months (Petersen et al, 1995;Saari et al, 2007). Therefore, the bone remodelling following joint replacement was simulated for a period equivalent to sixty months.…”
Section: Strain-adaptive Bone Remodelling Simulationmentioning
confidence: 98%